FAMILY BLEPHARICERIDAE - Gil-Azevedo, Leonardo H.; Santos, Durval Da S. (Zootaxa, 2016)
Blephariceridae are poorly known in Colombia, being reasonably well sampled only in Antioquia Department. In the present catalogue, five species of Limonicola Lutz and eight species of Paltostoma Schiner are reported for the country.